Metformin anticancer: Reverses tumor hypoxia induced by bevacizumab and reduces the expression of cancer stem cell markers CD44/CD117 in human ovarian cancer SKOV3 cells - Fan, Yuanchun; Cheng, Huimin; Liu, Yueping; Liu, Shihao; Lowe, Scott; Li, Yaru; Bentley, Rachel; King, Bethany; Tuason, John Pocholo W.; Zhou, Qin; Sun, Chenyu; Zhang, Hui (Frontiers in Pharmacology, 2022)
Background: The occurrence and development of solid tumors depend on the blood supply in the tumor microenvironment (TME). Blocking angiogenesis is a new therapeutic strategy to inhibit tumor growth. The anti-angiogenic drug bevacizumab has been approved for gynecological malignancies, especially for advanced recurring cervical cancers and recurring ovarian cancers (OC). Studies in OC have shown a limited effect of bevacizumab in the general population, with a slight improvement in progression-free survival (PFS) and no effect on overall survival (OS). This might be related to the bevacizumab’s role in aggravating the hypoxia in the TME, which helps maintain the stemness of ovarian cancer stem cells (CSCs) and promotes the invasion and metastasis of cancer cells. Drugs that target CSCs, such as metformin, may enhance the efficacy of anti-vascular therapies. Therefore, this study aimed to evaluate the effect of metformin combined with bevacizumab on the proliferation of OC cells both in vitro and in vivo, as well as on tumor hypoxia and tumor stem cell markers of human ovarian cancer SKOV3 cells. Methods: The OC cell model SKOV3 was treated with metformin, bevacizumab, and cisplatin alone or in combinations. Cell Counting Kit-8 (CCK-8) was used to measure the rate of cell proliferation. Metformin and bevacizumab were studied in vivo in nude mice. SKOV3 cells were transplanted subcutaneously in nude mice, and different drug interventions were performed after tumor formation, including blank control, bevacizumab alone, metformin alone, cisplatin alone, bevacizumab + metformin, bevacizumab + cisplatin, metformin + cisplatin, and bevacizumab + metformin + cisplatin treatments. The growth of transplanted tumors was routinely monitored and visualized by the tumor growth curve. We used flow cytometry to examine the proportion of CD44+/CD117+ CSCs in each group. The immunohistochemistry (IHC) method was applied to detect expressions of vascular endothelial growth factor (VEGF), hypoxia-inducible factor 1α (HIF-1α), and microvascular density-associated factor CD34 in tumor cells. The limit dilution method was used to re-inject tumor cells in nude mice to examine the tumor recurrence rate. Results: Combination therapy of metformin and bevacizumab significantly reduced the proliferation rate of SKOV3 cells and the growth rate of transplanted tumors in nude mice compared with the monotherapy effects. In vivo results showed that metformin significantly reduced the proportion of CD44+/CD117+ CSCs (p < 0.01). Although bevacizumab increased the proportion of CD44+/CD117+ CSCs, the addition of metformin did offset this fluctuating trend. The combination of bevacizumab, metformin, and cisplatin efficiently decreased the proportion of CSCs in the OC animal model. IHC results exhibited that expressions of VEGF, CD34, and HIF-1α in transplanted tumors were decreased by metformin alone compared with the control (p < 0.05). In the bevacizumab treatment, VEGF, and CD34 expressions were decreased, while that of HIF-1α was increased, suggesting that the degree of hypoxia was differentially aggravated after the bevacizumab treatment. The VEGF, CD34, and HIF-1α expressions in the bevacizumab + metformin + cisplatin group were the lowest among all other treatment groups (p < 0.05). Subcutaneous statistics of nude mice reseeded by the limit dilution method showed that the tumor recurrence rate in the bevacizumab + metformin + cisplatin group was relatively lower. Conclusion: Metformin, bevacizumab combined with platinum-based chemotherapy can significantly inhibit the growth of ovarian cancer cells and transplanted tumors, which is due to the reduction of the proportion of CD44+/CD117+ CSCs and the alleviation of hypoxia in the tumor microenvironment. Therefore, this may be a reasonable and promising treatment regimen.